Law‐books, concomitant texts and ethnically framed legal pluralism on the fringes of post‐Carolingian Europe: northern Italy and Catalonia around 1000. (Early Medieval Europe, 2022)
Around 1000, a new type of law‐book emerged in Catalonia and northern Italy that attests to new ways of handling legal material. Incorporating in full the Visigothic and Lombard law codes, respectively, these law‐books provided a base for studying and interpreting old law through comments, glosses etc., addressing new users such as lay judges. By looking at the Catalonian Liber iudicum popularis and the north Italian Liber Papiensis in their manuscript contexts along with several revealing concomitant texts, the article seeks to demonstrate that these law‐books also need to be understood as reflecting a transformation of law brought about by the two regions' former belonging to the Carolingian empire. A manuscript‐based approach can demonstrate how the local appropriation of pre‐Carolingian and Carolingian traditions contributed to the legitimization of post‐Carolingian rule in both regions, whose legal cultures evolved quite differently despite numerous parallels and points of comparison.